Effects of the Polyherbal Wattana Formula on Food Intake, Intestinal Transit, and Ileum Contraction in Wistar Rats - Pinpat Tripatara; Pruksa Chotitham; Tassanee Paraput; Pravit Akarasereenont (Tehran University of Medical Sciences, 2024)
The polyherbal Wattana formula (WNF) has been used in traditional practice for over 30 years to promote health and prevent age-related issues. However, no scientific evidence supports its efficacy, including its impact on the gastrointestinal system in older individuals. This study examined the effects of WNF on intestinal transit, body weight, and food intake in Wistar rats that received oral WNF at doses of 100, 300, or 1000 mg/kg for 14 days. Following treatment, the small intestine was isolated, and intestinal transit was assessed via charcoal meal travel distance. Compared to the vehicle, 1000 mg/kg WNF significantly reduced intestinal transit in the charcoal meal test and decreased body weight. Additionally, 600 µg/mL WNF extract impeded acetylcholine-induced ileum smooth muscle contraction ex vivo. WNF at all doses demonstrated no effects on food intake. Our findings suggest that WNF may have potential antidiarrheal effects and benefits in weight management and abdominal spasm reduction.